Analyzing Figurative Language and Writer’s Emotion in Paul Mauriat’s Love is Blue - Aldha Williyan; Retno Purwani Sari; Nessa Yuanita; Riksan Nawawi Fahrul Padri (Departement of Mathematics Education, 2023)
Songwriters utilize figurative language to portray their ideas, sentiments, and emotions in a manner that is more intriguing, attractive, and distinctive. This encourages this research to study a song written by Paul Mauriat entitled